Nano-enzyme-loaded bionic hydrogel as well as preparation method and application thereof

Through the preparation method of loaded nanoenzyme bionic hydrogel, the nanoenzyme formed by Mn@Co@MOF and Pt nanoparticles combined with sodium alginate is solved, and the problems of microenvironmental regulation and bone tissue repair of diabetic bone inflammation are achieved. The effective regulation of bone inflammation and the promotion of bone tissue repair significantly improve the treatment efficiency and safety.

CN119214995AActive Publication Date: 2024-12-31SICHUAN UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411388454.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-31
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

The microenvironmental regulation and bone tissue repair problems caused by diabetes have many challenges in traditional treatment methods, especially when bone tissue repair ability declines in hyperglycemia.

Method used

Using the preparation method of loaded nanoenzyme bionic hydrogel, Mn@Co@MOF nanocomposites were pyrolyzed to obtain Mn@Co3O4 powder, combined with Pt nanoparticles to form nanoenzymes, and combined with sodium alginate and 3-aminophenylboronic acid. A catalytically active hydrogel is formed, and the supported nanoenzyme bionic hydrogel is soaked in CaCl2 solution to achieve regulation of the osteoinflammatory microenvironment and promote bone tissue repair.

Benefits of technology

显著减轻炎症反应,提高骨组织修复和再生效率,纳米酶的高效催化性能和良好生物相容性确保了水凝胶在生物医学应用中的安全性和有效性,有效调控糖尿病引起的骨炎症微 environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119214995A_ABST
    Figure CN119214995A_ABST
Patent Text Reader

Abstract

The invention discloses nano-enzyme-loaded bionic hydrogel and a preparation method and application thereof, and belongs to the technical field of biological composites.The preparation method comprises the following steps that Mn-Co-MOF powder, Mn-Co3O4 powder and Pt nano particles are prepared, Mn-Co3O4-Pt nano-enzyme is prepared, a Mn-Co3O4-Pt nano-enzyme-PVA mixed solution is prepared, an Alg-PBA hydrogel precursor is prepared, and the nano-enzyme-loaded bionic hydrogel is obtained. The nano-enzyme-loaded bionic hydrogel disclosed by the invention can effectively regulate and control a bone inflammation microenvironment caused by diabetes mellitus, remarkably relieve inflammatory response and promote bone tissue repair and regeneration. The nano-enzyme loaded in the hydrogel has efficient catalytic performance, simulates the catalytic function of the enzyme, and improves the treatment efficiency. Meanwhile, the good biocompatibility of the nano-enzyme ensures the safety and effectiveness of the hydrogel in biomedical application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biocomposite materials, and specifically relates to a nanoenzyme-loaded bionic hydrogel and a preparation method and application thereof. Background Art

[0002] With the development of biomaterials science and nanotechnology, functional porous materials have shown great application potential in the biomedical field. In particular, metal organic frameworks (MOFs) and their derivatives have become a hot topic of research due to their unique porous structure, high specific surface area and adjustable chemical composition. MOFs are not only widely used in catalysis, gas storage and separation, but their derived nanozymes have also attracted much attention due to their catalytic activity of mimicking enzymes.

[0003] In the biomedical field, nanozymes are widely studied for disease treatment and biosensing due to their efficient catalytic performance and good biocompatibility. In particular, for diabetic bone defects, traditional treatments face many challenges due to the inflammatory response and decreased bone tissue repair ability caused by the high blood sugar environment. Therefore, it is particularly important to develop a new material that can simultaneously regulate the inflammatory microenvironment and promote bone tissue repair. Summary of the invention

[0004] The purpose of the present invention is to provide a nanozyme-loaded bionic hydrogel and a preparation method and application thereof. The nanozyme-loaded bionic hydrogel has a regulating effect on the bone inflammation microenvironment caused by diabetes and has a promoting effect on osteogenesis.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0006] A method for preparing a nanozyme-loaded bionic hydrogel comprises the following steps:

[0007] S1. Disperse MnCl2·4H2O, Co(NO3)2·6H2O and 2-methylimidazole in anhydrous methanol respectively, quickly mix the solution, transfer the mixed solution to a reactor, heat, centrifuge, collect the precipitate, repeatedly wash with anhydrous methanol, and dry to obtain Mn@Co@MOF powder;

[0008] S2, placing the Mn@Co@MOF nanocomposite material obtained in step S1 in a tube furnace, heating, burning, and pyrolyzing to obtain Mn@Co3O4 powder;

[0009] S3, dissolving chloroplatinic acid in deionized water, adding polyvinyl pyrrolidone, and stirring thoroughly to obtain Pt nanoparticles;

[0010] S4, dispersing the Mn@Co3O4 powder obtained in step S2 in RO water, adding Pt nanoparticles, stirring at 1500-2000 rpm for 18 h, and collecting the precipitate by centrifugation to obtain Mn@Co3O4@Pt nanozyme;

[0011] S5, dispersing the Mn@Co3O4@Pt nanozyme obtained in step S4 in RO water to obtain a nanozyme suspension, adding PVA, stirring evenly, and obtaining a mixed solution;

[0012] S6, dissolving sodium alginate, EDC·HCl, and 3-aminophenylboronic acid in deionized water, stirring, placing in a 3500 kd dialysis bag, dialyzing with RO water for 7 days, and freeze-drying to obtain an Alg-PBA hydrogel precursor;

[0013] S7. Dissolve the Alg-PBA hydrogel precursor obtained in step S6 in RO water, mix with the mixed solution obtained in step S5 in equal volumes, stir evenly, add 0.1M NaOH aqueous solution, stir, and soak in a 1% CaCl2 aqueous solution to load the nanozyme biomimetic hydrogel.

[0014] Preferably, in step S1, the mixed solution is transferred to a reaction kettle, heated at 25° C., and reacted for 12 hours.

[0015] Preferably, in step S1, the centrifugation parameter is 5000-7000 rpm, and the centrifugation time is 15-20 min.

[0016] Preferably, in step S1, after repeated washing with anhydrous methanol, the solid product is dried at 20-25° C. for 24 hours.

[0017] Preferably, in step S2, the Mn@Co@MOF powder is placed in a tubular furnace, heated to 500°C at a rate of 40°C / min in a nitrogen environment, and burned for 3 hours to obtain Mn@Co3O4 powder by pyrolysis.

[0018] Preferably, in step S6, the stirring process parameters are: stirring rate is 800-1000 rpm / min, and stirring time is 18-24 h.

[0019] Preferably, in step S6, the process parameters of the freeze-drying process are: pre-freezing at -40°C for 180 min, vacuum freeze drying at -80°C, freeze drying for 48 h, and a vacuum degree of 9 Pa.

[0020] Preferably, in step S7, the soaking time in the 1% by mass CaCl2 aqueous solution is 30 seconds.

[0021] The present invention also provides a nanozyme-loaded bionic hydrogel prepared by the preparation method.

[0022] The present invention also provides a nanozyme-loaded bionic hydrogel prepared by the preparation method or use of the nanozyme-loaded bionic hydrogel in preparing a product for alleviating and / or treating diabetic bone defects.

[0023] Compared with the prior art, the present invention has the following advantages and technical effects:

[0024] The present invention discloses a nanozyme-loaded bionic hydrogel and a preparation method thereof, wherein the nanozyme-loaded bionic hydrogel achieves effective regulation of the bone inflammation microenvironment caused by diabetes, significantly reduces the inflammatory response, and promotes bone tissue repair and regeneration. The nanozyme loaded in the hydrogel has efficient catalytic performance, simulates the catalytic function of the enzyme, and improves the treatment efficiency. At the same time, the good biocompatibility of the nanozyme ensures the safety and effectiveness of the hydrogel in biomedical applications.

[0025] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Statistical graph of the effect of Mn@Co@MOF on the activity of nanozyme superoxide dismutase (SOD) provided in Examples 1-4;

[0027] Figure 2 A statistical graph of the GOx-like catalytic activity of the Mn@Co3O4 nanozyme provided in Example 5 and the Mn@Co3O4@Pt nanozyme provided in Example 6;

[0028] Figure 3 Statistical graph of the SOD-like catalytic activity of the Mn@Co3O4 nanozyme provided in Example 5 and the Co3O4 nanozyme provided in Example 7;

[0029] Figure 4 The CAT-like catalytic activity of the Mn@Co3O4 nanozyme provided in Example 5 and the Co3O4@C nanozyme provided in Example 8;

[0030] Figure 5 The Aln functional molecule release curve of the Mn@Co3O4@Pt nanozyme provided in Example 6;

[0031] Figure 6 Mg of Mn@Co3O4@Pt nanozyme provided in Example 6 2+ Functional molecule release profile;

[0032] Figure 7 The rheology-frequency scanning diagram of the composite hydrogel provided in Example 9 and Example 10;

[0033] Figure 8The rheology-time scanning diagram of the composite hydrogel provided in Example 9 and Example 10;

[0034] Fig. 9 A comparison chart of the compression modulus of the composite hydrogel PAA provided in Example 9 and Example 10;

[0035] Fig.10 This is a statistical graph showing the effect of the PAM composite hydrogel provided in Example 9 on M1 macrophage iL-1;

[0036] Fig.11 Statistical graph showing the effect of the PAM composite hydrogel provided in Example 9 on the M1 macrophage pro-inflammatory marker iNOS

[0037] Fig.12 This is a statistical graph showing the effect of the PAM composite hydrogel provided in Example 9 on M2 macrophage CD206;

[0038] Fig.13 This is a statistical graph showing the effect of the PAM composite hydrogel provided in Example 9 on the M2 macrophage pro-inflammatory marker iL-10;

[0039] Fig.14 The immunofluorescence results of the PAM composite hydrogel provided in Example 9 on the M1 macrophage pro-inflammatory marker iNOS, wherein: Fig.14 a in the figure is the immunofluorescence result on the 3rd day. Fig.14 b in the figure is the immunofluorescence result on day 5;

[0040] Fig.15 The immunofluorescence results of the PAM composite hydrogel provided in Example 9 on M2 macrophage CD206, wherein: Fig.15 a in the figure is the immunofluorescence result on the 3rd day. Fig.15 b in the figure is the immunofluorescence result on day 5;

[0041] Fig.16 A statistical graph showing the expression of ALP, a marker related to osteogenic differentiation, by the PAM composite hydrogel provided in Example 9;

[0042] Fig.17 A statistical graph showing the expression of the osteogenic differentiation-related marker OPN by the PAM composite hydrogel provided in Example 9;

[0043] Fig.18 A statistical graph showing the expression of the osteogenic differentiation-related marker Runx-2 by the PAM composite hydrogel provided in Example 9;

[0044] Fig.19 A statistical graph showing the expression of the osteogenic differentiation-related marker OCN by the PAM composite hydrogel provided in Example 9;

[0045] Fig. 20 The immunofluorescence results of the PAM composite hydrogel provided in Example 9 for osteogenic differentiation-related markers, wherein: Fig. 20 a in the figure is the immunofluorescence result on the 7th day. Fig. 20 b in the figure is the immunofluorescence result on day 14;

[0046] Fig.21 The results of the PAM composite hydrogel provided in Example 9 on the osteogenic differentiation-related marker ALP / ARS, wherein: Fig.21 a in is the ALP result, Fig.21 b in the figure is the ARS result;

[0047] Fig. 22 A micro-CT image of the PAM composite hydrogel provided in Example 9;

[0048] Fig.23 A statistical graph of bone volume fraction of the PAM composite hydrogel provided in Example 9;

[0049] Fig.24 A statistical graph of the degree of separation of trabecular bone of the PAM composite hydrogel provided in Example 9;

[0050] Fig.25 This is a statistical graph of the number of trabecular bones in the PAM composite hydrogel provided in Example 9. DETAILED DESCRIPTION

[0051] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0052] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0053] The test materials used in the examples of the present invention are all conventional test materials in the art and can be purchased through commercial channels.

[0054] Example 1 This example provides a Mn@Co@MOF composite material

[0055] 1mmol MnCl2·4H2O and 1mmol Co(NO3)2·6H2O were dispersed in 4mL anhydrous methanol, and 49.9mmol 2-methylimidazole was dispersed in 26mL anhydrous methanol. The solution was quickly mixed and transferred to a reactor. The mixture was heated at 25°C for 12h and centrifuged at 5000rpm for 20min. The precipitate was collected and repeatedly washed with anhydrous methanol and dried at 25°C for 24h to obtain Mn@Co@MOF, i.e., M 10 C.

[0056] The preparation method of Example 2 is the same as that of Example 1, except that in step S1, the amount of MnCl2·4H2O added is 0 mmol, and Mn@Co@MOF, i.e., M0C, is obtained.

[0057] The preparation method of Example 3 is the same as that of Example 1, except that in step S1, the amount of MnCl2·4H2O added is 0.2 mmol, and Mn@Co@MOF, namely M2C, is obtained.

[0058] The preparation method of Example 4 is the same as that of Example 1, except that in step S1, the amount of MnCl2·4H2O added is 0.5 mmol, and Mn@Co@MOF, namely M5C, is obtained.

[0059] Example 5 This example provides a Mn@Co3O4 nanozyme

[0060] S1. Disperse 0.5mmol MnCl2·4H2O and 1mmol Co(NO3)2·6H2O in 4mL anhydrous methanol, and disperse 49.9mmol 2-methylimidazole in 26mL anhydrous methanol. Quickly mix the solution, transfer the mixed solution to a reactor, heat at 25°C, react for 12h, centrifuge at 5000rpm for 20min, collect the precipitate, wash it repeatedly with anhydrous methanol, and dry it at 25°C for 24h to obtain Mn@Co@MOF, namely M5C.

[0061] S2. Place the M5C obtained in step S1 in a tubular furnace, heat it to 500°C at a rate of 40°C / min in a nitrogen environment, burn it for 3 hours, and pyrolyze it to obtain Mn@Co3O4 nanozyme.

[0062] Example 6 This example provides a Mn@Co3O4@Pt nanozyme

[0063] S1. Disperse 0.5mmol MnCl2·4H2O and 1mmol Co(NO3)2·6H2O in 4mL anhydrous methanol, and disperse 49.9mmol 2-methylimidazole in 26mL anhydrous methanol. Quickly mix the solution, transfer the mixed solution to a reactor, heat at 25°C, react for 12h, centrifuge at 5000rpm for 20min, collect the precipitate, wash it repeatedly with anhydrous methanol, and dry it at 25°C for 24h to obtain Mn@Co@MOF, namely M5C.

[0064] S2. Place the M5C obtained in step S1 in a tube furnace, heat it to 500°C at a rate of 40°C / min in a nitrogen environment, burn it for 3 hours, and pyrolyze it to obtain Mn@Co3O4 powder.

[0065] S3, dissolving chloroplatinic acid in deionized water, adding polyvinyl pyrrolidone, and stirring thoroughly to obtain Pt nanoparticles;

[0066] S4. Disperse the Mn@Co3O4 powder obtained in step S2 in RO water, add Pt nanoparticles, stir at 2000 rpm for 18 h, collect the precipitate by centrifugation, and obtain Mn@Co3O4@Pt nanozyme, i.e., MCPt A.

[0067] Example 7 This example provides a Co3O4@C nanozyme

[0068] 1mmol Co(NO3)2·6H2O was dispersed in 4mL anhydrous methanol, and 49.9mmol 2-methylimidazole was dispersed in 26mL anhydrous methanol. The solution was quickly mixed, and the mixed solution was transferred to a reactor, heated at 25°C, reacted for 12h, centrifuged at 5000rpm for 20min, and the precipitate was collected and repeatedly washed with anhydrous methanol. It was dried at 25°C for 24h to obtain Co3O4, and then the product was placed in a tubular furnace, heated to 500°C at a rate of 40°C / min in a nitrogen environment, calcined for 3h, and pyrolyzed to obtain Co3O4@C powder.

[0069] Example 8 This example provides a Co3O4

[0070] Disperse 1mmol Co(NO3)2·6H2O in 4mL anhydrous methanol, and 49.9mmol 2-methylimidazole in 26mL anhydrous methanol. Mix the solution quickly, transfer the mixed solution to a reactor, heat at 25°C, react for 12h, centrifuge at 5000rpm for 20min, collect the precipitate, wash it repeatedly with anhydrous methanol, and dry it at 25°C for 24h to obtain Co3O4.

[0071] Example 9 This example provides a biomimetic hydrogel loaded with nanozymes

[0072] S1. Disperse 0.5mmol MnCl2·4H2O and 1mmol Co(NO3)2·6H2O in 4mL anhydrous methanol, and disperse 49.9mmol 2-methylimidazole in 26mL anhydrous methanol. Quickly mix the solution, transfer the mixed solution to a reactor, heat at 25°C, react for 12h, centrifuge at 5000rpm for 20min, collect the precipitate, wash it repeatedly with anhydrous methanol, and dry it at 25°C for 24h to obtain Mn@Co@MOF, namely M5C.

[0073] S2, placing the M5C obtained in step S1 in a tube furnace, heating it to 500°C at a rate of 40°C / min in a nitrogen environment, burning it for 3h, and pyrolyzing it to obtain Mn@Co3O4 powder;

[0074] S3, dissolving chloroplatinic acid in deionized water, adding polyvinyl pyrrolidone, and stirring thoroughly to obtain Pt nanoparticles;

[0075] S4, dispersing the Mn@Co3O4 powder obtained in step S2 in RO water, adding Pt nanoparticles, stirring at 2000 rpm for 18 h, and collecting the precipitate by centrifugation to obtain Mn@Co3O4@Pt nanozyme

[0076] S5. Disperse 100 mg of Mn@Co3O4@Pt nanozyme obtained in step S4 in 10 mL of RO water to obtain a nanozyme suspension, add 1 g of PVA, stir evenly, and obtain a mixed solution;

[0077] S6, 2.0 g sodium alginate, 1.92 g EDC·HCl, and 0.78 g 3-aminophenylboronic acid were dissolved in 200 mL deionized water, stirred at 1000 rpm / min for 18 h, placed in a 3500 kd dialysis bag for RO water dialyzation for 7 days, pre-frozen at -40°C for 180 min, and vacuum freeze-dried at -80°C for 48 h, wherein the vacuum degree was 9 Pa, to obtain an Alg-PBA hydrogel precursor;

[0078] S7. Dissolve the Alg-PBA hydrogel precursor obtained in step S6 in RO water to prepare an Alg-PBA aqueous solution with a mass fraction of 10%, mix it with the mixed solution obtained in step S5 in equal volumes, stir it evenly, add 0.1M NaOH aqueous solution, stir it, and soak it in a 1% CaCl2 aqueous solution with a mass fraction for 30 seconds to obtain a PAM composite hydrogel.

[0079] The preparation method of Example 10 is the same as that of Example 9, except that when preparing the mixed solution in step S5, Mn@Co3O4@Pt nanozyme is not added to obtain the PA composite hydrogel.

[0080] The effects of the above embodiments are verified by the following experiments:

[0081] 1. Determine the effect of Mn@Co@MOF provided in Example 1-4 on the activity of nanoenzyme superoxide dismutase (SOD). The Shanghai ELISA SOD activity detection kit was used for determination. The results are as follows Figure 1 .

[0082] Depend on Figure 1 It can be seen that the nanozyme SOD synthesized by M5C, that is, the MnCl2·4H2O addition ratio is 0.5mmol, has the best SOD activity, and this ratio of nanozyme was selected for subsequent experiments.

[0083] 2. Determine the glucose oxidase (GOx)-like catalytic activity, SOD-like catalytic activity, and catalase (CAT)-like catalytic activity of the nanozymes provided in Examples 5-7. The test scheme is as follows:

[0084] The GOx-like catalytic activity of the Mn@Co3O4 of Example 5 and the Mn@Co3O4@Pt nanozymes of Example 6 was tested by catalytic oxidation of TMB, wherein the same buffer, glucose, and RO water of the same volume as the sample were added as the control group, 3mL HAC-NaAc buffer (0.1M, pH 4.0), 20μL of a certain concentration of sample and 80μL of glucose (12.0mM) were added in sequence, incubated at 37°C for 30min, 200μL of 2mM TMB was added, the absorbance was detected at 652nm, and the UV spectra were scanned by UV spectrometer. The results are shown in Figure 2 .

[0085] Depend on Figure 2 It can be seen that the Mn@Co3O4@Pt provided in Example 6 can catalyze the decomposition of glucose into hydrogen peroxide, and then catalyze the oxidation of TMB, showing the characteristic ultraviolet absorption peak of ox-TMB at 652nm. The control group and the Mn@Co3O4 provided in Example 5 had no absorption peak, which verified the GOX activity of Mn@Co3O4@Pt.

[0086] The SOD-like catalytic activity of Mn@Co3O4 in Example 5 and Co3O4 in Example 7 was tested by a SOD assay kit (MLbio) according to the instructions, wherein an equal volume of RO water as the material group solution was used as the control group. The results are shown in Figure 3 .

[0087] Depend on Figure 3 It can be seen that Mn@Co3O4 can remove superoxide anions (O 2- ), (O 2- It can reduce nitroblue tetrazolium to generate blue formazan, which absorbs at 560nm. SOD can remove O 2- , thereby inhibiting the formation of formazan; Mn doping improves the SOD activity of the material and reduces the ultraviolet absorption at 560nm.

[0088] The CAT-like catalytic activity of Mn@Co3O4 in Example 5 and Co3O4@C in Example 8 was tested by measuring the O2 concentration every hour through a dissolved oxygen meter until 6 hours, with RO water of the same volume as the sample as the control group. The results are shown in Figure 4 .

[0089] Depend on Figure 4 It can be seen that the amount and rate of oxygen released within 6h of Mn@Co3O4 are the highest. Mn doping improves the CAT activity of the material and can catalyze the decomposition of hydrogen peroxide.

[0090] 3. Test the Mn@Co3O4@Pt nanozyme provided in Example 6 for Aln and Mg 2+ Release curve of functional molecules. The test scheme is as follows:

[0091] 15 mg Aln, 50 mg MgCl2, and 100 mg Mn@Co3O4@Pt nanozyme were added to 10 mL pH 5.0 phosphate buffer and stirred overnight at room temperature. The mixture was centrifuged at 13000 rpm and washed with RO water for 3 times. The precipitate was collected by centrifugation and dried to obtain the product powder. 2+ Controllable loading of functional molecules, testing Aln and Mg by ICP-MS (inductively coupled plasma mass spectrometry) in weakly alkaline buffer (PBS, pH 7.4) 2+ Release curve of functional molecules. Figure 5 and Figure 6 .

[0092] Depend on Figure 5 It can be seen that Aln is first released rapidly within the first 15 days and then slowly released until it is basically completely released after 24 days, which verifies the loading of Aln in Mn@Co3O4@Pt and its effective release under normal physiological conditions.

[0093] Depend on Figure 6 It can be seen that Mg 2+ The rapid release in the first 13 days and then the slow release until the release is almost complete in 24 days confirms that Mg 2+ Loading in Mn@Co3O4@Pt and effective release under normal physiological conditions.

[0094] 4. The rheological and mechanical properties of the composite hydrogels provided in Examples 9 and 10 were characterized. The test scheme was as follows: a rheometer and a DMA dynamic mechanical analyzer were used to measure the rheological and mechanical properties of the hydrogels. The results are shown in FIG. Figure 7-9 .

[0095] Depend on Figure 7 It can be seen that at different scanning frequencies, the storage modulus of the hydrogel is greater than the loss modulus, and the hydrogel can be stably gelled.

[0096] Depend on Figure 8 It can be seen that under continuous shear force changes, the storage modulus of the hydrogel is continuously greater than the loss modulus, and the hydrogel can be stably gelled.

[0097] Depend on Fig. 9 It can be seen that the PAM provided in Example 9 and the PA provided in Example 10 have similar compression modulus and similar mechanical strength, with PAM being slightly higher than PA. This may be because the doping of nanomaterials improves the mechanical properties of the composite hydrogel to a certain extent.

[0098] 5. Regulation of the inflammatory microenvironment: The experimental plan is as follows:

[0099] 400μM H2O2 was added to the macrophage (RAW264.7) culture environment (DMEM, 10% of FBS, 100U / mL penicillin, 100μg / mL streptomycin) to simulate the inflammatory environment. The nanozyme was co-incubated with RAW264.7 in a H2O2 environment, and the M1 macrophages and their pro-inflammatory markers (iL-1, iNOS) and M2 macrophages and their anti-inflammatory markers (CD206, iL-10) were characterized by cell molecular analysis methods such as qRT-PCR and immunofluorescence (Scale bar = 20μm) analysis to explore the effect of nanozyme-loaded hydrogels on macrophage polarization and the regulatory performance on the inflammatory microenvironment. The qRT-PCR results are shown in Figure 2. Figure 10-13 , immunofluorescence Figure 14-15 .

[0100] Depend on Figure 10-13 It can be seen that the H2O2 environment can induce the expression of pro-inflammatory factors (IL-1, iNOS) in RAW264.7 and inhibit the expression of anti-inflammatory factors (IL-10, CD206), while the hydrogel loaded with Mn@Co3O4@Pt nanozymes can alleviate this induction and restore it to normal levels. Mn@Co3O4@Pt can promote the expression of anti-inflammatory factors (IL-10, CD206) and inhibit the expression of pro-inflammatory factors (IL-1, iNOS) in an inflammatory environment.

[0101] Depend on Figure 14-15 It can be seen that the H2O2 environment can induce the expression of pro-inflammatory factors (iNOS) in RAW264.7 and inhibit the expression of anti-inflammatory factors (CD206), while the hydrogel loaded with Mn@Co3O4@Pt nanozymes can alleviate this induction and restore it to normal levels. MCPtA can promote the expression of anti-inflammatory factors (CD206) and inhibit the expression of pro-inflammatory factors (iNOS) in an inflammatory environment.

[0102] 6. Research on the regulatory performance of bone immune microenvironment. The experimental plan is as follows:

[0103] Bone marrow mesenchymal stem cells (rBMSCs) were cultured in osteogenic medium (α-MEM, 10mMβ-glycerophosphate, 50μg / mL ascorbic acid and 10nM dexamethasone), and 50mM glucose was added to simulate a high-sugar environment. Nanozymes were added to co-culture with rBMSCs, and the expression of osteogenic differentiation-related markers (Runx-2, OCN, OPN, ALP) was analyzed by qRT-PCR, immunofluorescence (Scale bar = 20μm), ALP / ARS (Scale bar = 500μm), etc., to explore the mechanism by which nanozymes promote osteogenesis through a synergistic bone immune microenvironment regulation strategy in vitro. The qRT-PCR results are shown in Figure 16-19 , immunofluorescence results are as follows Fig. 20, ALP / ARS results are as follows Fig.21 .

[0104] Depend on Figure 16-19 It can be seen that the H2O2 environment inhibits the osteogenic differentiation of rBMSCs and downregulates the gene expression of osteogenic-related factors OPN, OCN, RUNX-2, and ALP, while the hydrogel loaded with Mn@Co3O4@Pt nanozymes can alleviate this inhibition and restore it to normal levels. Due to the osteogenic components doped in the material, it can promote the expression of related factors.

[0105] Depend on Fig. 20 It can be seen that the H2O2 environment inhibits the osteogenic differentiation of rBMSCs. Immunofluorescence shows that the H2O2 environment inhibits the protein expression of the osteogenic factor OPN, while the hydrogel loaded with Mn@Co3O4@Pt nanozyme can alleviate this inhibition and restore it to normal levels. Due to the osteogenic components doped in the material, the expression of OPN is promoted.

[0106] Depend on Fig.21 It can be seen that the H2O2 environment inhibits the osteogenic differentiation of rBMSCs. In the ALP and ARS staining at 7 days and 14 days, no obvious alkaline phosphatase and calcium nodule formation were observed. The H2O2 environment inhibits the maturation and formation of osteoblasts, while the hydrogel loaded with Mn@Co3O4@Pt nanozymes can alleviate this inhibition and restore it to normal levels. Due to the osteogenic components doped in the material, the maturation of osteoblasts is promoted. In the ALP and ARS staining, obvious alkaline phosphatase and calcium nodule formation can be seen.

[0107] 7. Evaluation of the repair effect of diabetic bone defects. The test plan is as follows:

[0108] A diabetic SD rat model was established by streptozotocin injection. After sodium pentobarbital anesthesia, a circular incision with a diameter of 5 mm was made in the median area of ​​the skull in the anterior-posterior direction. Rats were injected with antibiotics after surgery to prevent wound infection. The loaded nanozyme bionic hydrogel was implanted into the skull defect site, and then the rats were killed at 4, 8, and 12 weeks. The skull tissue was taken and fixed with 4% paraformaldehyde. Micro-CT (Scale bar = 1 mm) and supporting software were used for three-dimensional reconstruction, and related parameters such as bone volume fraction, trabecular separation, and trabecular number were measured. After 12 weeks of implantation of the material, the bone volume fraction of the material-filled group increased by 85.3% compared with the non-implanted group, and increased by 35.3% compared with the non-diabetic material implanted group. The regulation of the material's bone inflammatory microenvironment and the promotion of osteogenesis were further verified in vivo. The micro-CT results are as follows Fig. 22 The bone volume fraction results are as follows Fig.23 The results of trabecular separation are as follows Fig.24 The results of trabecular number are as follows Fig.25 .

[0109] Depend on Fig. 22 It can be seen that from 4 to 12 weeks, the healing rate of skull defects in rats in the diabetic group was slow, which was similar to that in the simple PA hydrogel-doped group. However, the healing effect of skull defects in rats in the MCPtA-doped PAM composite hydrogel group was ideal. At 8 weeks, the healing of skull defects was close to that of the control group of non-diabetic rats, and at 12 weeks, it was higher than the normal group and almost completely healed. This is related to the fact that MCPtA improves the diabetic microenvironment and has an osteogenesis-promoting effect.

[0110] Depend on Fig.23 It can be seen that at 12 weeks, the bone volume / total volume (BV / TV) (4.98% ± 1.78%) was 1.32 times higher than that at 4 weeks, while the PA group (11.4% ± 0.93%) was 1.43 times higher than that at 4 weeks. The control group showed a normal process of bone regeneration, with BV / TV at 12 weeks (17.2% ± 4.05%) being 1.99 times higher than that at 4 weeks, while composite hydrogel implantation significantly weakened the inhibition and promoted bone regeneration, reaching 32.5% ± 4.01%, which was 3.26 times that at 4 weeks, 2.47 times that of the diabetes group, and 1.64 times that of the control group at 12 weeks.

[0111] Depend on Fig.24 It can be seen that at 12 weeks, the trabecular bone separation (Tb.SP) of the composite hydrogel-doped group was significantly lower than that of the unfilled diabetic group, verifying the in vivo skull repair effect of the composite hydrogel in diabetic rats.

[0112] Depend on Fig.25 It can be seen that the number of trabeculae (Tb.N) in the composite hydrogel-doped group was significantly higher than that in the unfilled diabetic group at 12 weeks, verifying the in vivo skull repair effect of the composite hydrogel in diabetic rats.

[0113] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a nanozyme-loaded bionic hydrogel, characterized in that: The steps include: S1. Disperse MnCl2·4H2O, Co(NO3)2·6H2O and 2-methylimidazole in anhydrous methanol respectively, quickly mix the solution, transfer the mixed solution to a reactor, heat, centrifuge, collect the precipitate, repeatedly wash with anhydrous methanol, and dry to obtain Mn@Co@MOF powder; S2, placing the Mn@Co@MOF nanocomposite material obtained in step S1 in a tube furnace, heating, burning, and pyrolyzing to obtain Mn@Co3O4 powder; S3, dissolving chloroplatinic acid in deionized water, adding polyvinyl pyrrolidone, and stirring thoroughly to obtain Pt nanoparticles; S4, dispersing the Mn@Co3O4 powder obtained in step S2 in RO water, adding the Pt nanoparticles obtained in step S3, stirring at 1500-2000 rpm for 18 h, and collecting the precipitate by centrifugation to obtain Mn@Co3O4@Pt nanozyme; S5, dispersing the Mn@Co3O4@Pt nanozyme obtained in step S4 in RO water to obtain a nanozyme suspension, adding PVA, stirring evenly, and obtaining a mixed solution; S6, dissolving sodium alginate, EDC·HCl, and 3-aminophenylboronic acid in deionized water, stirring, placing in a 3500 kd dialysis bag, dialyzing with RO water for 7 days, and freeze-drying to obtain an Alg-PBA hydrogel precursor; S7. Dissolve the Alg-PBA hydrogel precursor obtained in step S6 in RO water, mix with the mixed solution obtained in step S5 in equal volumes, stir evenly, add 0.1M NaOH aqueous solution, stir, and soak in a 1% CaCl2 aqueous solution to load the nanozyme biomimetic hydrogel.

2. The preparation method according to claim 1, characterized in that: In step S1, the mixed solution is transferred to a reaction kettle, heated at 25° C., and reacted for 12 h.

3. The preparation method according to claim 1, characterized in that: In step S1, the centrifugation parameters are 5000-7000 rpm, and the centrifugation time is 15-20 min.

4. The preparation method according to claim 1, characterized in that: In step S1, after repeated washing with anhydrous methanol, the solid product is dried at 20-25° C. for 24 hours.

5. The preparation method according to claim 1, characterized in that: In step S2, the Mn@Co@MOF powder is placed in a tubular furnace, heated to 500°C at a rate of 40°C / min in a nitrogen environment, and burned for 3 hours to obtain Mn@Co3O4 powder by pyrolysis.

6. The preparation method according to claim 1, characterized in that: In step S6, the stirring process parameters are: stirring rate is 800-1000 rpm / min, and stirring time is 18-24h.

7. The preparation method according to claim 1, characterized in that: In step S6, the process parameters of the freeze-drying process are: pre-freezing at -40°C for 180 minutes, vacuum freeze drying at -80°C, freeze drying for 48 hours, and a vacuum degree of 9Pa.

8. The preparation method according to claim 1, characterized in that: In step S7, the immersion time in the 1% by mass CaCl2 aqueous solution is 30 seconds.

9. The nanozyme-loaded bionic hydrogel prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the nanozyme-loaded bionic hydrogel prepared by the preparation method according to any one of claims 1 to 8 or the nanozyme-loaded bionic hydrogel according to claim 9 in preparing products for alleviating and / or treating diabetic bone defects.

Citation Information

Patent Citations

  • Platinum nanoparticle / nitrogen point nano-enzyme and preparation method and application thereof

    CN111208105A

  • Microenvironment-responsive multifunctional injectable hydrogel as well as preparation method and application thereof

    CN116785228A

  • Application of doping-based multi-enzyme active nano material in treatment of inflammatory diseases

    CN117731693A

  • Bionic nano drug delivery system based on metal organic framework and preparation method of bionic nano drug delivery system

    CN117899045A

  • MOF nano-enzyme as well as preparation method and application thereof

    CN118059942A